Implementasi Metode Pembelajaran Al-Qur'an Hadis di Madrasah Aliyah Negeri 1 Konawe Selatan - Shinta Elfan Khairat (Tarbiyatul Akhyar: Jurnal Pendidikan, 2026)
This researcher aims to describe the implementation of Al-Qur'an Hadith learning and to find out the Al-Qur'an Hadith learning methods at MAN 1 Konawe Selatan. This type of research uses descriptive qualitative. The research location is MAN 1 South Konawe, Tanea Village, Konda District, South Konawe Regency. The data and data sources consist of primary data and secondary data. As well as data collection techniques through observation, interviews, and documentation. The data analysis techniques through data collection, data reduction, and data presentation. The triangulation used is source triangulation, technical triangulation and time triangulation. The results of the research are the implementation of Al-Qur'an Hadith learning methods which are carried out in accordance with educational procedures, considering several learning methods used by teachers such as lecture methods, discussions, demonstrations. The implementation of the Al-Qur'an Hadith learning method at MAN 1 Konawe Selatan has been carried out because the learning carried out by Al-Qur'an Hadith teachers can achieve learning objectives and can be practiced in everyday life. Implementation of Al-Qur'an Hadith learning at MAN 1 Konawe Selatan, teachers always learn the abilities of their students so that what is conveyed by the teacher can be understood by their students. Because in the teaching and learning process teachers and students play an important role in interacting in class. Inhibiting factors in the implementation of Al-Qur'an Hadith learning such as lack of motivation from the students themselves, lack of understanding of makharijul huru in Al-Qur'an and Hadith verses are the main factors inhibiting the implementation of learning. Because in Al-Qur'an Hadith subjects students are led to memorize, read, and identify verses of Al-Qur'an and Hadith in Al-Qur'an Hadith subjects.